MENINGKATKAN KEPERCAYAAN DIRI PADA ANAK-ANAK REMAJA YANG TINGGAL DI PANTI ASUHAN X - Agustina; Stevanie Ho; Ellen Angelina; Celvin Stivanus (Jurnal Serina Abdimas, 2025)
Adolescents living in orphanages often face psychological challenges, including low self-confidence due to limited social environments and emotional support. Based on observations and interviews at Orphanage X, it was found that most teenagers experience difficulties in self-expression and feel unequal compared to their peers at school. This humanitarian project aimed to enhance adolescents’ self-confidence through a psychoeducational approach and public speaking practice. The methods used included observation, interviews, pre-tests and post-tests based on Lauster’s theory, and the implementation of three core programs: a seminar on self-confidence, a presentation on self-confidence using PowerPoint, and vlog creation. The activities were conducted over a period of three months with weekly visits. Evaluation results showed an increase in the average self-confidence score from 62.27 in the pre-test to 68.82 in the post-test. The vlog activity was the most favored program as it provided a space for the children to express themselves creatively and freely. In conclusion, public speaking training and digital self-expression activities proved to be effective in improving the self-confidence of adolescents in the orphanage. The program also contributed to fostering a more open and supportive social atmosphere among the children. ABSTRAK Remaja yang tinggal di panti asuhan kerap menghadapi tantangan psikologis, termasuk rendahnya kepercayaan diri akibat keterbatasan lingkungan sosial dan dukungan emosional. Berdasarkan observasi dan wawancara di Panti Asuhan X, ditemukan bahwa sebagian besar anak remaja mengalami kesulitan dalam mengekspresikan diri dan merasa tidak setara dengan teman sebaya mereka di sekolah. Proyek kemanusiaan ini bertujuan untuk meningkatkan kepercayaan diri remaja melalui pendekatan psikoedukatif dan praktik public speaking. Metode yang digunakan mencakup observasi, wawancara, pre-test dan post-test berbasis teori Lauster, serta pelaksanaan tiga program inti: seminar tentang kepercayaan diri, presentasi mengenai materi kepercayaan diri menggunakan PowerPoint, dan pembuatan vlog. Kegiatan dilaksanakan selama tiga bulan dengan kunjungan mingguan. Hasil evaluasi menunjukkan adanya peningkatan skor rata-rata kepercayaan diri dari 62,27 pada pre-test menjadi 68,82 pada post-test. Aktivitas vlog menjadi program paling diminati karena memberi ruang bagi anak-anak untuk berekspresi secara kreatif dan bebas. Kesimpulannya, pelatihan public speaking dan ekspresi diri berbasis media digital terbukti efektif dalam meningkatkan rasa percaya diri remaja di panti. Program ini juga berdampak pada tumbuhnya suasana sosial yang lebih terbuka dan suportif antar anak.